(untitled) (REMUNOM, 2026)
Access to water is a fundamental human right, yet it faces challenges that have persisted for centuries. In this context, social workers, acting within communities and public policies, play a strategic role in identifying vulnerabilities, promoting equity, and defending the right to water. This study analyzes the contribution of social workers in the formulation and evaluation of public policies aimed at the sustainable management of water resources, utilizing sociodemographic indicators alongside biological and physicochemical markers. Adopting a qualitative approach, we conducted a systematic literature review across national and international scientific databases, employing PRISMA and PICO methodologies, as well as VOSviewer software for bibliometric mapping. Preliminary results indicate that while Social Work intervention in the water sector still lacks robust theoretical consolidation, it is essential for integrating social dimensions into technical and environmental analyses. Furthermore, the use of indicators and markers proved relevant in drafting more inclusive and sustainable policies, thereby enhancing water security and social well-being. We conclude that strengthening this agenda is indispensable for facing contemporary challenges and ensuring social justice regarding water access.